Validating oil and gas royalty rate measurement scale: evidence from Nigeria / Abba Ya’u, Natrah Saad and Abdussalam Mas’ud - Ya’u, Abba; Saad, Natrah; Mas’ud, Abdussalam (Faculty of Accountancy, 2019)
There is rising concern over the lack of scales on the oil and gas company’s royalty rate compliance by host oil and gas countries. This study attempts to validate royalty rate compliance scale by means of rigorous scale validation procedures. Therefore, an adapted questionnaire comprising seven (7) items was administered to 184 local and multinational oil and gas companies in Nigeria. All the items were subjected to evaluations and validations by 8 experts reviewers with cognate experience in oil and gas activities. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis using SPSS version 25, indicator reliability, internal consistency Using PLS SEM were used to analyze the data. The results provide evidence that the royalty rate compliance scale have achieved a reliable and valid factor structure. Consequently, Policymakers, government, practitioners and researchers can adapt this scale to assess royalty rate compliance by oil and gas companies in different jurisdictions across the globe. This study undoubtedly builds the existing literature and contributes to the subject area, which by implication will enhance the fiscal policies arrangement and practice of petroleum producing countries.